Utilization of telemedicine in conjunction with wearable devices for patients with chronic musculoskeletal pain: a randomized controlled clinical trial - Kazuhiro Hayashi; Kenji Miki; Yukiko Shiro; Tomoko Tetsunaga; Toshifumi Takasusuki; Masako Hosoi; Masao Yukioka (Scientific Reports)
Abstract The present randomized controlled trial aimed to investigate the effects of home-based telemedicine with wearable devices and usual care on pain-related outcomes in patients with chronic musculoskeletal pain, compared to usual care alone. The patients with chronic musculoskeletal pain were randomly allocated to the usual care group or the telemedicine group, which participated in telemedicine with wearable devices, the objective data from which were recorded, in conjunction with usual care for six months. The primary outcome measure was the Numeric Rating Scale (NRS) for pain. The secondary outcome measures were the Pain Catastrophizing Scale (PCS), Hospital Anxiety and Depression Scale (HADS), Pain Disability Assessment Scale (PDAS), and EuroQol-five dimensions-three level (EQ-5D-3L). Seventy-one participants were analyzed. At 1 and 3 months, there were no significant differences in the NRS scores between the groups; however, the telemedicine group had a significantly superior effect on all of the outcome measures at 6 months compared to the usual care group. The number of steps and distance were significantly increased at 6 months compared to baseline in the telemedicine group. Home-based telemedicine with wearable devices and usual care has a modest effect on pain-related outcomes compared to usual care in patients with chronic musculoskeletal pain. This study was registered (UMIN000052994 - 04/12/2023).